Pengaruh Kepemimpinan Transformasional Kepala Sekolah Terhadap Keberhasilan Perubahan Kurikulum di MA Plus Taruna Teknik Aljabbar - Sinta Nuriah Hasibuan; Fitri yulia; Nurhalimah harahap (Jurnal Pendidikan Agama Islam, 2026)
The success of curriculum change is inseparable from the leadership of the qualified principal. One of the principal leadership models that is in accordance with the MBS program is the transformational leadership style. This study aims to determine the influence of the principal's transformational leadership on the success of curriculum change at the MA Plus Taruna Teknik Al Jabbar school. The formulation of the research problem is whether there is an influence of the principal's transformational leadership on the success of curriculum change at the MA Taruna Teknik Al Jabbar school. This study was conducted using a quantitative approach. The population of this study was all teachers at the MA Plus Taruna Teknik Al Jabbar school, totaling 30 people. The sample was selected using Area sampling and Simple random sampling techniques, totaling 28 teachers. Data were collected through a Likert scale model questionnaire with validity and reliability having been tested. Data analysis used correlation and regression techniques with the help of the SPSS version 22 program. The results of the study showed that the transformational leadership of the madrasah principal influenced the success of curriculum change at the MA Plus Taruna Teknik Al Jabbar school.